Aerosol size distributions at Syowa Station and Dome Fuji Station, Antarctica - Masahiko Hayashi; Yasunori Matsumoto; Naohiko Hirasawa; Takashi Yamanouchi; Yasunobu Iwasaka (National Institute of Polar Research, 2010)
Simultaneous observations of the aerosol size distribution for diameters of 0.003-5.0 μm were performed at Syowa Station (69゜00′S, 39゜35′E, 15 m a.s.l.) and Dome Fuji Station (77゜19′S, 39゜42′E, 3810 m a.s.l.) in Antarctica from February 1997 to January 1998. Size distributions show composites of a small-Aitken mode (less than 0.05 μm in diameter), a large-Aitken mode (0.05-0.3 μm in diameter), and a large giant particle mode (larger than 0.3 μm in diameter). Concentrations of small and large Aitken modes were high in summer and low in winter. On the other hand, concentrations of large giant particle mode were low in summer and high in winter. The high and or low concentration events for one or a few days in whole size range were observed especially in winter. High concentration events in small Aitken mode with the low concentrations in diameter of 0.07-5.0 μm were also observed at Dome Fuji Station in spring. Meteorological conditions during the events at Dome Fuji Station were different from those at at Syowa station.